STRATEGI COPYWRITING KONTEN INSTAGRAM @RPNHOSPITALITY UNTUK PROMOSI DAN BRANDING ASET HOSPITALITY PT RPN - maharani, maylani (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2025)
This research deeply examines the copywriting strategies implemented in the Instagram content @rpnhospitality within the context of promoting and branding hospitality assets managed by PT RPN. The primary problem explored is how copywriting is effectively used to attract a diverse audience, build engagement, and ultimately achieve the established marketing objectives. The research methodology applied is the descriptive qualitative method, involving a series of in-depth interviews with the IT division and the multimedia team responsible for content creation, as well as the managers of PT RPN's hospitality assets, with the aim of gaining a comprehensive understanding of the planning, production, and evaluation processes of Instagram content. The research results consistently demonstrate that @rpnhospitality adopts the AIDAS (Attention, Interest, Desire, Action, Satisfaction/Share) approach comprehensively and integrally in their copywriting strategies. Each AIDAS element is carefully implemented to create content that not only attracts initial audience attention but is also effective in generating interest through the presentation of relevant information, fostering desire for the products or services offered, encouraging concrete actions such as reservations or visits, and most importantly, building customer satisfaction through an emphasis on quality and perceived benefits. The research confirms the crucial role of copywriting in dynamic digital marketing with a relevant emotional touch and recommends the continued development of more personalized, creative, and informative strategies, with a stronger focus on building emotional connections with audiences and creating message consistency across social media.